Analisis Beban Kerja Mental pada Operator Dump Truck dengan Metode Nasa-TLX - Muh Anhar; Darsini; Muhadi (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
Human Resources (HR) are workers, employees, or laborers working at a company. HR is one of the vital aspects of a company to increase the effectiveness and efficiency of a company. PT. Saptaindra Sejati (PT. SIS) is a coal mining company located in Kalimantan. Operators are parts of company human resources who have important roles in the production. Fatigue can cause excessive mental workload and decline productivity. This study focuses on the mental workload of dump truck operators. It aims to identify the mental workload level of dump truck operators using the NASA-TLX method. The result indicated that the mental workload level indicator is in the high category. The highest indicator is Frustration Level (FR) with a value of 24%, followed by Mental Demand (MD) and Effort (EF) (17%), Own Performance (OP) (16%), and Physical Demand (PD) and Temporal Demand (PD) (13%).